2021
DOI: 10.54028/nj202120103
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Envelope Designs to Maximize Residential Cooling Energy Savings in Bangkok Neighborhoods

Abstract: Architectural design can significantly improve home energy-efficiency. New energy-saving techniques are regularly proposed; however, integrating all design parameters into the energy simulation specific knowledge and is time-consuming, making it difficult for non-experts in building energy analysis. This present study investigates the impact of envelope designs on household cooling energy consumption in housing complexes located in Bangkok neighborhood areas. The study selects a representative house and identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 14 publications
0
4
0
Order By: Relevance
“…We selected a base case from a previous study that surveyed countless detached houses around the Bangkok Metropolitan Area (Inprom & Jareemit, 2021). The representative two-storied house (Figure 1) has dimensions of 9.20 x 8.00 m and consists of three bedrooms and three bathrooms.…”
Section: Methodology Identifying a Base Case And Case Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…We selected a base case from a previous study that surveyed countless detached houses around the Bangkok Metropolitan Area (Inprom & Jareemit, 2021). The representative two-storied house (Figure 1) has dimensions of 9.20 x 8.00 m and consists of three bedrooms and three bathrooms.…”
Section: Methodology Identifying a Base Case And Case Studiesmentioning
confidence: 99%
“…The opening size influences the ventilation rate and therefore represents another significant factor that affects the infection. A sliding window was specified in this study as it is almost the only window type found in typical houses (Inprom & Jareemit, 2021). We selected four window sizes that are most common in typical houses for this study (Table 1).…”
Section: Methodology Identifying a Base Case And Case Studiesmentioning
confidence: 99%
“…MehdiTavakolan et al [16] used EnergyPlus for dynamic simulation to perform comprehensive simulation analysis of possible scenarios to improve the energy efficiency of the building. Daranee Jareemit [17] used the eQuest model to examine residential cooling energy consumption. Increases in the solar heat gain coefficient of the In 2018, China's building operation carbon emissions totaled around 2.1 billion tons, accounting for almost 20% of the country's total emissions.…”
Section: Introductionmentioning
confidence: 99%
“…MehdiTavakolan et al [16] used EnergyPlus for dynamic simulation to perform comprehensive simulation analysis of possible scenarios to improve the energy efficiency of the building. Daranee Jareemit [17] used the eQuest model to examine residential cooling energy consumption. Increases in the solar heat gain coefficient of the windows, the U-value of the walls, and the length of the eaves can reduce energy consumption and increase the building's energy efficiency, according to the findings.…”
Section: Introductionmentioning
confidence: 99%